Surgical Outcomes of Clival Chordoma Through Endoscopic Endonasal Approach: A Single-Center Experience - Chen, Ge; Li, Mingchu; Xu, Wenlong; Wang, Xu; Feng, Ming; Wang, Renzhi; Liu, Xiaohai (Frontiers in Endocrinology, 2022)
Objective: Clival chordoma is a locally aggressive tumor with low metastatic potential. In the past decade, endoscopic transnasal surgery (ETS) for clival chordoma has had a higher resection rates and a lower morbidity rates than transcranial approaches. Here, we present our initial single-center experience after ETS of clival chordomas. Patients and methods: This study retrospectively analyzed 17 patients with clival chordoma who received ETS in our department between March 2015 and September 2021. The operation was performed by a single surgeon with binnostril endoscopic transnasal approach. The clinical and pathological characteristics were analyzed along with the surgical outcomes and complications. Results: A total of 17 patients with clival chordoma received ETS with a median follow-up of 29.2 months (range 1-79). Gross total resection (GTR) was performed in 7 cases (41%), subtotal resection (STR) in 7 case (41%) and partially resection (PR) in 3 cases (18%). Cerebrospinal fluid leakage occurred in 2 cases (12%) and meningitis developed in 3 patients (18%). There were no new focal neurological deficits postoperatively. Four in 7 patients with STR have had radiotherapy while the other three chose to be monitored. Till the last follow-up, three patients in STR group who received radiotherapy (3 in 4) had no tumor regrowth, while one in STR group with radiotherapy (1 in 4) showed tumor progression. Two patients in STR group without radiotherapy (2 in 3) showed stable tumor while the left one (1 in 3) showed tumor progression. One patient in the PR group died of tumor progression 2 years postoperation and the other one showed tumor progression and died of lung cancer 1 year postoperation. In addition, 1 in 7 patients with GTR had tumor recurrence in situ after 10 months and developed surgical pathway seeding in the spinal canal in C1 after 16 months. No recurrence occurred in the other 6 cases with GTR during the follow-up. Conclusion: Endoscopic transsphenoidal surgery is a safe and reliable method for clival chordoma with high resection rates and low morbidity rates. GTR without tumor residuum would improve the outcome although more cases are needed.